A Comprehensive Review On Trivrit (Operculina Turpethum Syn. Ipomoea Turpethum) - KOHLI K R; NIPANIKAR S U; KADBHANE K P (International Journal of Pharma and Bio Sciences, 2010)
Trivrit (Operculina turpethum syn. Ipomoea turpethum) is commonly used since centuries in Ayurvedic system of Medicine to treat fevers, edema, ascites, anorexia, constipation, hepatosplenomegaly, intoxication, haemorrhoids, fistula, anemia, obesity, abdominal tumors, ulcers/wounds, worm infestation, pruritus and other skin disorders. It is the best amongst the herbs used for Virechana (i.e. therapeutic purgation), one of the procedures of Ayurvedic Panchakarma therapy. This review comprehensively incorporates the phramacognosy, medicinal uses, and pharmacology of O. turpethum. Few preclinical studies done on Operculina turpethum have shown that it possesses anti-inflammatory, anticancer, cytotoxic, antisecretory, ulcer protective, hepatoprotective, & antibacterial activities. Some preliminary clinical studies have reported laxative, anti-inflammatory, analgesic, anti-helminthic and anti-arthritic effects of its crude root powder. The herb merits further research as it may be a source of potential anticancer and anti-rheumatic agent(s). As the plant Operculina turpethum is endangered, also prompt attention needs to be given to protect it from extinction.